Variations in activity of Ru/TiO(2 )and Ru/Al2O3 catalysts for CO2 hydrogenation: an investigation by in-situ infrared spectroscopy studies - Dongapure, Pavan; Bagchi, Sayan; Mayadevi, S.; Devi, R. Nandini (Molecular Catalysis, 2020)
CO2 hydrogenation to methane, an important reaction strategically and also for value adding to CO2, is investigated on two different catalysts, Ru supported on alumina as well as titania to understand better low temperature activity of Ru/TiO2 catalyst. In-situ infrared studies are carried out in three different steps, viz., (i) CO2 adsorption on fully reduced catalyst (ii) reaction of these adsorbed species with gaseous H-2 and (iii) under co-feed of CO2 and H-2, at different temperatures. On Ru/Al2O3 catalyst, CO2 reacts with hydroxyls on the support surface to form carbonate and adsorbs reductively on metal as CO. Further reduction to formate and methyl species occurs on reaction with H. Small concentration of the reactive intermediate formyl forms only at high temperatures. Whereas, bare TiO2 itself seems capable of reductive adsorption of CO2 as formate indicating enhanced reducibility of titania based catalyst. Formyl groups are observed at low temperatures in Ru/TiO2 in step (ii), which further forms methyl and gaseous methane at much lower temperatures when compared to alumina catalyst. Highly reactive CO species loosely bound to metal-support interface observed at high temperatures, which is not present on Ru/Al2O3 catalyst also makes this catalyst superior. In comparison, linearly bound CO seen in alumina catalyst is not as reactive.
Keywords: CO2 hydrogenation; In-situ infra red spectroscopy; Ru/Al2O3; Ru/TiO2

Effect of B site substitution in Gd2B2-xNiyO7-delta (B= Ti, Zr) ternary metal oxide catalysts in dry reforming of methane - Ghodke, Seema R.; Thundiyil, Shibin; Dongapure, Pavan; Devi, R. Nandini (Molecular Catalysis, 2022)
Structured catalysts are emerging as active and durable catalysts in dry reforming of methane due to their inherent characteristics like lattice insertion of active metals and consequent stability imparted. Here we report Ti and Zr substituted Gd2B2-xNiyO7-delta (B = Ti, Zr) catalysts synthesized by citrate gel method, which are characterized and tested for dry reforming of methane. Structure and Ni substitution has been confirmed by Rietveld refinement of powder XRD patterns and Raman analysis. TPR and CO2-TPD were performed to analyze the reducibility and effect of basic sites of catalysts in DRM activity. Ni doped Ti analogue shows stable and superior activity towards dry reforming of methane for 100 h. The in situ IR studies and XPS analysis confirmed the presence of surface hydroxyl species in this catalyst, which triggers the activation of CO2 and provides higher and durable activity in dry reforming reaction. Absence of any C formation in this catalyst after durability test indicates the mechanism of C gasification by the surface hydroxyl species enhancing stable activity for long durations.
Keywords: A(2)B(2)O(7); Citrate gel method; Dry reforming of methane; Ternary metal oxide

Mechanistic insights into near ambient pressure activity of intermetallic NiZn/TiO2 catalyst for CO2 conversion to methanol - Dongapure, Pavan; Tekawadia, Jyoti; Thundiyil, Shibin; Caha, Ihsan; Deepak, Francis Leonard; Devi, R. Nandini (ChemCatChem, 2023)
Ni-Zn pair is predicted through descriptor-based studies to be conducive for CO2 hydrogenation. In this study, NiZn (1 : 1) intermetallics supported on TiO2 is identified as a potential candidate for near ambient pressure activity. The effect of reduction temperature on the catalyst textural properties as well as on CO2 to methanol reduction are explored. Structural and microscopic studies provide clear evidence of phase evolution of NiZn alloy with increasing reduction temperatures, along with phase variations of Zn based oxides. Interface between NiZn intermetallics and ZnO nanoparticles observed at reduction temperature of 550 degrees C, seems to play a crucial role in making this system most active and selective to methanol. In addition, in-situ IR studies provide mechanistic insights and indicates the formation of methanolic species even at ambient pressure.
Keywords: CCUS; CO2; In-situ IR; Methanol; near ambient pressure

Deciphering the role of chemisorbed CO in CO2 methanation: kinetic and mechanistic investigation over monometallic (Ru) and bimetallic (Ru-Ni) catalysts - Dongapure, Pavan; Tekawadia, Jyoti; Naidu, V. Satyam; Devi, R. Nandini (Catalysis Science & Technology, 2024)
Supported metal catalysts have made prominent contributions to CO2 mitigation through conversion into useful chemicals. However, intermediates and mechanisms involved in this process remain ambiguous. Herein, we present the kinetics, mechanistic route and impact of chemisorbed CO in CO2 methanation on Ru/gamma-Al2O3 and Ru-Ni/gamma-Al2O3 catalysts. Both the catalysts show minimal variation in adsorbed species on changing the duration of reduction, as confirmed through in situ IR spectroscopy. A notable observation is that the adsorbed CO exhibits a red shift at a longer reduction time and a more reactive nature on the Ru/gamma-Al2O3 surface. Conversely, stable bridged CO mode is detected on Ru-Ni/gamma-Al2O3 under similar conditions, leading to catalyst poisoning in all instances. This indicates that pre-reduction duration does not have much effect on the surface but interference of CO has more effect at lower concentrations of reactant gases. In situ XRD analysis reveals limited changes in the metallic or mixed oxide species during these conditions. Reaction kinetic analysis showed that Ru-Ni/gamma-Al2O3 has better rate performance at higher concentrations of CO2, whereas Ru/gamma-Al2O3 exhibits better rate performance at lower concentrations. The activation energy was found to be 74.07 kJ per mole for Ru/gamma-Al2O3 and 89.38 kJ per mole for Ru-Ni/gamma-Al2O3. The turnover frequency (TOF) is directly proportional to the rate of formation of methane.

Experimental and kinetic modelling studies for the design of fixed bed methanol reactor over CuZA catalyst - Bagwan, Farahanaz M.; Dongapure, Pavan; Kulkarni, Amol A.; Vasireddy, Satyam Naidu (Chemical Engineering Research Design, 2024)
Direct conversion of CO 2 via hydrogenation to value-added chemicals is a vital approach for utilising CO 2 emitted into the atmosphere. In this paper, a critical analysis of reaction kinetic modelling studies is explored in a fixed bed reactor to improve methanol yield for different H 2 to CO 2 ratios by simulating a lab-scale reactor for adiabatic and isothermal conditions. The feed inlet temperature and pressure variations are applied to study the effect of both configurations on methanol production. The results show that the isothermal configuration yields 2.76% more methanol yield compared to the adiabatic reactor. The effect of H 2 to CO 2 molar ratios of 3, 6 and 9 on the performance of the catalyst and the influence of CO and CO 2 hydrogenation is investigated with model simulations. The overall methanol yield is increased from 19.03% to 36.41% with increase in H 2 to CO 2 molar ratio from 3 to 9. Experiments are performed using commercial copper-based catalyst for different temperatures of 210, 230 and 250 degrees C at a pressure of 40 bar for H 2 /CO 2 of 3 and GHSV of 720 h -1 as well as at optimal temperature of 250 degrees C and 50 bar with varying H 2 /CO 2 of 3, 6, 9 for 3 g and 6 g catalyst. The maximum methanol yield of 2.53% and space time yield of 13.59 mg/g cat .h is obtained at H 2 /CO 2 ratio of 9.
Keywords: CO2 conversion; CuZA catalyst; H2 toCO2 molar ratio; Kinetic modelling; Methanol